Quercetin treatment against ischemia/reperfusion injury in rat corpus cavernosum tissue: a role on apoptosis and oxidative stress - ŞENER, TARIK EMRE (TAYLOR & FRANCIS LTD, 2013)
Reactive oxygen metabolites play an important role in the ischemia/reperfusion (I/R)-induced tissue injury. This study was designed to investigate the possible protective effects of quercetin against I/R injury of the rat corpus cavernosum tissue. To induce I/R injury, abdominal aorta was clamped for 30 min and reperfused for 60 min. Quercetin (20 mg/kg) or vehicle was given before ischemia and just after reperfusion in the I/R group and in the sham-operated control group in which clamping was not performed. After decapitation, corpus cavernosum tissues were removed and either placed in organ baths or stored for evaluating biochemical parameters. Oxidative injury was examined by measuring lucigenin chemiluminescence (CL), nitric oxide (NO), malondialdehyde (MDA) and glutathione (GSH) levels, superoxide dismutase (SOD) and myeloperoxidase (MPO) activities and caspase-3 protein levels. In the I/R group, contractile responses to phenylephrine and relaxation responses to carbachol were impaired significantly compared with those in the control groups, while quercetin treatment in I/R group reversed both of the responses. On the other hand, increase in lucigenin CL, NO, MDA levels and MPO and caspase-3 activities and decrease in GSH levels and SOD activity in the cavernosal tissues of the I/R group were also significantly reversed by quercetin treatment. Furthermore, observed distorted morphology with ruptured endothelial cells and vacuolization in the cytoplasm of cavernosal tissues of I/R no longer persisted in the quercetin-treated I/R group. Thus, our results suggested that treatment with quercetin may have some benefits in controlling I/R-induced tissue injury through its anti-inflammatory, anti-apoptotic, and antioxidant effects.
Keywords: quercetin; ischemia/reperfusion; antioxidant; apoptosis; inflammation; corpus cavernosum; ERECTILE DYSFUNCTION; PENILE ARTERIES; PROTECTIVE ROLE; NITRIC-OXIDE; ISCHEMIA; ANTIOXIDANT; MELATONIN; MYELOPEROXIDASE; INFLAMMATION; MECHANISMS